ENSIKLOPEDIA DIGITAL TARI TIGA SERANGKAI MELAYU SEBAGAI SUMBER BELAJAR BAGI SISWA KELAS X SEKOLAH MENENGAH ATAS DI KOTA MEDAN - Dea Dwi Ananda; Martozet Martozet (Gesture: Jurnal Seni Tari, 2020)
ABSTRACT This study aims to describe the steps for Packaging the Digital Encyclopedia of the Triple Dance of Malay as a source of learning for grade X students of high schools in Medan. The theory used to discuss this research is to use a theory from Wijayanti (2012) which reveals that packaging or packaging is an effort made by a company to provide information to each consumer about the products contained in it. This research makes products using packaging steps that will be made according to the development of Dick and Carey (2009) including: 1) Analysis of needs and goals (Identity instructional goal), 2) Conduct instructional analysis (Conduct instructional analysis), 3) Developing instruments (Develop assessment instruments), 4) Developing and selecting instructional materials (Develop and select instructional materials), 5) Developing instructional strategies (6) Developing and conducting formative evaluations (Design and conduct formative evaluations of instructions), and 7 ) Conduct instructional revisions (Revise instruction). The method used in this study is a qualitative method. The population is the students of dance education program at Medan State University while the research sample is two students of the 2015 Dance Education dance. Data collection techniques are carried out by means of observation, interviews, documentation, literature studies, research instruments using instrument validation assessment sheets of media experts and instrument sheets expert material validation assessments and data analysis techniques. These data are then analyzed using qualitative descriptive methods. The results of this study are to produce learning material products for KD 3 delivery on the description of Malay society, the characteristics of motion, motion techniques, the Malay triad dance procedure that can be seen through a digital encyclopedia that has been packaged. Keywords: Digital Encyclopedia, Malay Triad Dance, Learning Centers.    ABSTRAKPenelitian ini bertujuan untuk mendeskripsikan langkah-langkah Pengemasan Ensiklopedia Digital Tari Tiga Serangkai Melayu sebagai sumber belajar bagi siswa kelas X Sekolah Menengah Atas di Kota Medan. Teori yang digunakan untuk membahas penelitian ini yaitu menggunakan teori dari Wijayanti (2012) yang mengungkapkan bahwa kemasan atau pengemasan adalah upaya yang dilakukan oleh perusahaan untuk memberikan informasi kepada setiap konsumennya tentang produk yang ada didalamnya. Penelitian ini membuat produk dengan menggunakan langkah-langkah pengemasan yang akan dibuat sesuai pengembangan Dick dan Carey (2009) diantaranya: 1) Analisis kebutuhan dan tujuan (Identity instructional goal), 2)Melakukan analisis instruksional (Conduct instructional analysis), 3) Mengembangkan instrumen (Develop assesment instruments), 4) Mengembangkan dan memilih material instruksional (Develop and select instructional materials), 5) Mengembangkan strategi instruksional (Develop Instructional Strategy), 6) Merancang dan melakukan evaluasi formatif (Design and conduct formative evaluation of instruction), dan 7) Melakukan revisi instruksional (Revise instruction). Metode yang digunakan pada penelitian ini adalah metode kualitatif. Populasinya adalah mahasiswa Program Studi Pendidikan Tari Universitas Negeri Medan sedangkan sampel penelitiannya adalah dua orang mahasiswa Pendidikan Tari Stambuk 2015. Teknik pengumpulan data dilakukan dengan cara observasi, wawancara, dokumentasi, studi kepustakaan, instrumen penelitian yang menggunakan lembar instrumen penilaian validasi ahli media dan lembar instrumen penilaian validasi ahli materi dan teknik analisis data. Data-data ini kemudian dianalisis dengan metode deskriptif kualitatif. Hasil penelitian ini adalah menghasilkan produk materi pembelajaran untuk penyampaian KD. 3 tentang gambaran masyarakat Melayu, karakteristik gerak, teknik gerak, prosedur gerak tari tiga serangkai Melayu yang dapat dilihat melalui ensiklopedia digital yang sudah dikemas.  Kata Kunci : Ensiklopedia Digital, Tari Tiga Serangkai Melayu, Pusat Belaja.